A Implementation of West Manggarai Regent Regulation No. 58 of 2017 concerning Hotel and Restaurant Tax on Tour Ships - Ramadhan, Ivan; Azhar, Azhar (PERSPEKTIF, 2025)
This study examines the implementation of hotel and restaurant tax policies on tourist ships in West Manggarai Regency. This policy aims to optimize the potential of Regional Original Revenue (PAD) from the tourism sector, especially accommodation and restaurant services provided by tourist ships. Hill and Hupe used a reference to policy implementation theory to analyze this problem. Data is collected through document studies sourced from written documents or archives, newspapers, and published and qualitatively analyzed statistical data. The study results concluded that although online tax reporting systems have been implemented to improve efficiency, the realization of tax revenues often does not reach the target. Factors that hinder these achievements include low taxpayer compliance, lack of socialization, limited human resources in supervision, and lack of coordination between stakeholders. This study recommends increasing socialization, technical training for business actors, and strengthening stakeholder coordination to improve policy effectiveness. In addition, strict sanctions are needed for business actors who do not comply, and incentives are provided for those who fulfill their obligations. These findings are expected to be useful for local governments in managing tourism tax potential more optimally.